Evaluasi Kinerja Struktur Bangunan Tinggi dengan Analisis Pushover Menggunakan Aplikasi Pemodelan Struktur (Studi Kasus: The Venetian Tower) - Asmara, Kabul Budi; Isneini, Mohd.; D.W.S.B.U, Chatarina Niken (Universitas Lampung, 2021)
The Venetian Tower is one of the apartments with a height of 116.7 m that belongs to the categoryof risk II. To maintain the safety of its residents, the building must provide optimal performance.Pushover analysis is one of the methods used to analyze earthquake loads to determine thebehavior of building collapses. The aims of research to determine the level of structuralperformance, collapse patterns, and capacity of beams and columns.Based on the results of pushover analysis, obtained the value of the roof displacement 629.178 mmin the x direction and 759.87 mm in the y direction. The structure of Venetian Tower is at theperformance level of Immediate Occupancy, if the earthquake occurred on the scale of MMI VIIIor 6 S.R. The ductility level of the building structure is partial ductile, where the value of ductileratio is 1.0778 in the x direction and 1.2131 in the y direction. The collapse mechanism of thestructure indicates the mechanism of strong column weak beam, where the plastic hinges occurs inthe beam first.The beams reviewed using SNI 2847:2019 are safe against shear forces but not safe againstbending moments and torque. The cross-section of the columns reviewed meets the requirementsof style, geometry, and reinforcement ratio in accordance with SNI 2847:2019.